2021
DOI: 10.1186/s40798-021-00306-w
|View full text |Cite
|
Sign up to set email alerts
|

Posterior-Chain Resistance Training Compared to General Exercise and Walking Programmes for the Treatment of Chronic Low Back Pain in the General Population: A Systematic Review and Meta-Analysis

Abstract: Background While chronic exercise training has been demonstrated to be an effective non-pharmacological treatment for chronic low back pain (CLBP), there has been a relative lack of evidence or clinical guidelines for whether a posterior chain resistance training programme provides any benefits over general exercise (GE). Objectives To determine if chronic posterior chain resistance training (PCRT), defined as exercise programmes of ≥6 weeks durati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 52 publications
2
7
0
Order By: Relevance
“…For people living with painful chronic health conditions, the influence of exercise interventions on pain is equivocal, with mostly small to moderate but inconsistent effects (56) , suggesting that exercise alone may only have small positive effects on disability and limited effects on coping in those with low back pain (57) . The experience of participants in this study, suggests a greater reduction in back pain than previous studies using exercise and resistance training programs for the treatment of chronic low back pain (59,60) , however, mediators and moderators of this change are unclear.…”
Section: Discussionmentioning
confidence: 54%
“…For people living with painful chronic health conditions, the influence of exercise interventions on pain is equivocal, with mostly small to moderate but inconsistent effects (56) , suggesting that exercise alone may only have small positive effects on disability and limited effects on coping in those with low back pain (57) . The experience of participants in this study, suggests a greater reduction in back pain than previous studies using exercise and resistance training programs for the treatment of chronic low back pain (59,60) , however, mediators and moderators of this change are unclear.…”
Section: Discussionmentioning
confidence: 54%
“…Finally, our data suggests that the main features of the FM cluster, i.e., higher cardiorespiratory fitness and higher flexibility of the trunk than both the other clusters, may be the determining factors for reduced back pain in our sample. The impact of cardiorespiratory fitness on back pain has been confirmed previously: for instance, Tataryn et al [ 62 ] observed that general exercise and walking activities are more efficient than muscular training for reducing back pain. Furthermore, aerobic fitness and activities may prevent and reduce the effects of back pain through mechanisms such as increased blood perfusion in the area [ 63 ].…”
Section: Discussionmentioning
confidence: 56%
“…For low back pain, exercise on its own has only small positive effects on disability, and limited ffects on coping [41]. Although the mediators and moderators are unknown, the experience of participants in this study, however, suggests a greater reduction in back pain than previous studies using exercise and resistance training [66,67].…”
Section: Change In a Long-term Health Conditionmentioning
confidence: 61%